Supply Chain Management and MSMEs Growth in Developing Countries: A Focus on North Central Region of Nigeria - Okon, Emmanuel Okokondem (International Journal of Small and Medium Enterprises, 2018)
Today’s business environment for Micro, Small, and Medium Enterprises (MSMEs) as well as large, global companies is more fluid and complex than ever before. Companies are adapting their supply chains to respond to increasingly competitive market conditions and to deliver higher revenue and greater value to their shareholders and customers. The study employed retrospective design. Respondents were selected using purposive sampling to arrive at the desired sample of the owners of Micro, Small, and Medium Enterprises in selected states of the north-central Nigeria. The 5-point Likert scale was employed to allow for precise responses on some issues raised regarding their supply chain management. Given the data gathered and generally ranking the totality of the Micro, Small, and Medium Enterprises in terms of least performance based on the indicators used, the result shows that the Micro, Small, and Medium Enterprises performed least on Total Delivered Cost followed by Operating Costs, Performance to Plan, Inventory, Supply Variability, Demand Variability, and Customer Service. In order to succeed, Micro, Small, and Medium Enterprises in Nigeria, particularly in the north-central states need to be able to increase inventory velocity, achieve the shortest possible cycle times, continually improve their supplier performance and drive their sales and market share.